The Influence of Brand Equity and Direct Marketing on Purchase Interest That Impacts The Purchase Decision of Wardah Cosmetics Products At Abadi Store - Nurkariani, Ni Luh; Febriani , Komang Ayu Dina (Lembaga Riset dan Inovasi Al-Matani, 2024)
This study aims to determine the effect of brand equity and direct marketing on purchase intention which has an impact on purchasing decisions for wardah cosmetic products at the Abadi Singaraja Store. The population is all consumers at the Abadi Singaraja store, namely 1,766 and the sample in this study uses 94 consumers at the Abadi Singaraja store. The data analysis technique used in this research is Structural Equation Modeling (SEM) based on variance SEM, which is well known as Partial Least Square (PLS) visual version 3.0. The results of this study indicate that the effect of brand equity on purchasing decisions is positive and significant. The effect of direct marketing on purchasing decisions is positive and significant. The effect of brand equity on purchase intention is positive and significant. The effect of direct marketing on purchase intention is positive and significant. The effect of buying interest on purchasing decisions is positive and significant.